Direct observation of magnetoelastic coupling in a molecular spin qubit: new insights from crystal field neutron scattering data. Issue 15 (17th March 2023) - Dunstan, Maja A.; Giansiracusa, Marcus J.; Vonci, Michele; Calvello, Simone; Yu, Dehong; Soncini, Alessandro; Boskovic, Colette; Mole, Richard A.
Abstract : Magnetoelastic coupling has been investigated using inelastic neutron scattering. This has allowed the spin–phonon coupling of the candidate qubit Na9 [Ho(W5 O18 )2 ]·35D2 O to be determined in the absence of an applied magnetic field. Abstract : Single-molecule magnets are promising candidates for data storage and quantum computing applications. A major barrier to their use is rapid magnetic relaxation and quantum decoherence due to thermal vibrations. Here we report a reanalysis of inelastic neutron scattering (INS) data of the candidate qubit Na9 [Ho(W5 O18 )2 ]·35D2 O, wherein we demonstrate for the first time that magnetic relaxation times and mechanisms can be directly observed as crystal field (CF) peak broadening in INS spectra of a lanthanoid molecular system. The magnetoelastic coupling between the lower energy CF states and phonons (lattice vibrations) is determined by the simultaneous measurement of CF excitations and the phonon density of states, encoded within the same INS experiment. This directly results in the determination of relaxation coupling pathways that occur in this molecule. Such information is invaluable for the further advancement of SMMs and to date has only been obtained from techniques performed in external magnetic fields. Additionally, we determine a relaxation rate of quantum-tunnelling of magnetisation that is consistent with previously measured EPR spectroscopy data.